Beyond Stimulus Deprivation: Iron Deficiency and Cognitive Deficits in Postinstitutionalized Children. Issue 5 (5th March 2014) - Doom, Jenalee R.; Gunnar, Megan R.; Georgieff, Michael K.; Kroupina, Maria G.; Frenn, Kristin; Fuglestad, Anita J.; Carlson, Stephanie M.
<x xml:space="preserve">Abstract</x> Children adopted from institutions have been studied as models of the impact of stimulus deprivation on cognitive development (Nelson, Bos, Gunnar, & Sonuga‐Barke, 2011), but these children may also suffer from micronutrient deficiencies (Fuglestad et al., 2008). The contributions of iron deficiency (ID) and duration of deprivation on cognitive functioning in children adopted from institutions between 17 and 36 months of age were examined. ID was assessed in 55 children soon after adoption, and cognitive functioning was evaluated 11–14.6 months postadoption when the children averaged 37.4 months old (SD = 4.9). ID at adoption and longer duration of institutional care independently predicted lower IQ scores and executive function (EF) performance. IQ did not mediate the association between ID and EF.